Penggunaan Media Internet eXe-Learning Berbasis Masalah pada Materi Perubahan Lingkungan untuk Meningkatkan Hasil Belajar Siswa - Siti Azizah; Emah Khuzaemah; Ina Rosdiana Lesmanawati (Scientiae Educatia: Jurnal Pendidikan Sains, 2017)
The Use of Internet eXe-Learning Media Based on Problems on The Concept Environmental Change to Increase Learning Outcomes Students X SMA Negeri 8 Cirebon. This study was conducted to improve student learning outcomes by maximizing the utilization of technology. The purpose of this research is to study 1) student learning activities, 2) improvement of student learning outcomes, and 3) students’ responses to the use of internet eXe-Learning based problem. The population in this study were all students of class X SMA Negeri 8 Kota Cirebon. The research design used was pretest-posttest control group design with data collection technique using test, observation and questionnaire. Data were analyzed using Anates ver. 4.0 and SPSS ver. 21.0 software. The results showed 1) student learning activities using internet eXe-Learning media has increased in every meeting and the indicator; 2) improvement of students’ experimental class learning outcomes and increased statistical test results in sig. 0.049 < 0.05, meaning Ho is rejected and Ha accepted; 3) students’ responses to learning using eXe-Learning based internet media are included into strong and powerful criteria.